When Phones Take Over: How Self-Management Bridges the Gap to Communication - Nur Wahyunianti Dahri; Heru Kurnianto Tjahjono; Mohsin Shaikh; Muhammad Aqil; Mashitah Syam (Universitas Muhammadiyah Yogyakarta, 2025)
In the contemporary digital era, the pervasive use of smartphones, particularly among Generation Z, has become a prevalent phenomenon across various settings, including professional environments. One of the deleterious effects of this phenomenon is what has been termed